THE PROCESS OF SOCIAL EXCHANGE IN MARRIAGE WITHIN THE FANAN CUSTOMARY GROUP IN THE ARU ISLANDS - Rahel Adriana Gainaugasiray; Tonny Donald Pariela; Simona Christina Henderika Litaay; Jeffry EM Leiwakabessy (SOSIOEDUKASI, 2026)
This study examines the traditional marriage practices of the Fanan community in the Aru Islands, focusing on the Odar Serol ceremony as a form of honorable marriage. The research employs qualitative methods, including ethnographic observation, interviews with community members, and documentation of customary rituals. The findings reveal that Fanan marriage encompasses multiple dimensions: economic, symbolic, kinship, moral-social, and cultural transmission. Bridewealth serves not only as material provision but also as a moral and symbolic medium to reinforce family alliances, social obligations, and respect for cultural norms. Kinship networks formed through marriage strengthen solidarity, cooperation, and social cohesion within the community. Traditional leaders and family members play essential roles in mediating exchanges, ensuring compliance with customary rules, and maintaining the integrity of the marriage process. The study concludes that Fanan marriage functions as both a social institution and a mechanism for preserving cultural heritage, transmitting values intergenerationally, and sustaining communal harmony. Overall, the Odar Serol ceremony illustrates how marriage rituals integrate symbolic meaning, moral responsibility, and structured social exchange to reinforce collective identity and maintain societal equilibrium.